Brain-targeted delivery of doxorubicin using glutathione-coated nanoparticles for brain cancers. (June 2015) - Geldenhuys, Werner; Wehrung, Daniel; Groshev, Anastasia; Hirani, Anjali; Sutariya, Vijaykumar
Abstract Objectives: To prepare and characterize in vitro a novel brain-targeted delivery of doxorubicin using glutathione-coated nanoparticles (NPs) for the treatment of brain cancer. Methods: Doxorubicin-loaded NPs were prepared by the nanoprecipitation method using PLGA-COOH (dl-lactide-co-glycolide). The NPs were coated with a glutathione-PEG conjugate (PEG-GSH) in order to target delivery to the brain. The NPs were characterized via in vitro studies to determine particle size, drug release, cellular uptake, immunofluorescence study, cytotoxic assay, and in vitro blood–brain barrier (BBB) assay. Results: The NPs showed a particle size suitable for BBB permeation (particle size around 200 nm). The in vitro release profile of the NPs exhibited no initial burst release and showed sustained drug release for up to 96 h. The immunofluorescence study showed the glutathione coating does not interfere with the drug release. Furthermore, in vitro BBB Transwell™ study showed significantly higher permeation of the doxorubicin-loaded NPs compared with the free doxorubicin solution through the coculture of rat brain endothelial (RBE4) and C6 astrocytoma cells (p < 0.05). Conclusions: We conclude that the initial in vitro characterization of the NPs demonstrates potential in delivering doxorubicin to cancer cells with possible future application in targeting brain cancers in vivo.